STRATEGI KOMUNIKASI PENYULUH AGAMA ISLAM KANTOR URUSAN AGAMA KECAMATAN BESITANG DALAM PENCEGAHAN NARKOBA PADA PARA PELAJAR - Wahyu Ziaulhaq (JURNAL SOSIO-KOMUNIKA, 2022)
This  study describes the communication of Islamic  religious  instructors  in  the religious affairs  office  of  Besitang  sub-district  in  the  prevention  of  drugs  to  students.  Drugs  on students. The problem of drugs in Indonesia is still something that is urgent and complex. In the last decade this problem has become widespread. It is proven by the significant increase in the number of drug abusers or addicts, along with the increasing disclosure of drug crime cases,  which  are increasingly  diverse  in  pattern  and  the  more  massive  the  syndicate network is. The impact of drug abuse not only threatens the survival and future of the abuser, but also the future of the nation and state, regardless of social, economic, age or educational strata. The purpose of this study is to educate readers that socialization has great benefits for drug prevention. This type of research is a qualitative research that seeks to  explain  the  social  phenomena  that  are  developing  in  the  present  mass  and  then described based on the concepts and theories of communication strategies, theories of interpersonal communication and persuasive communication. The results of this study are first, socialization to adolescents with religious languages with a persuasive and humanist approach. Second, teenagers carry out useful activities such as attending lectures at mosques or recitation centers, doing sports and also honing skills in the arts. Third, the family plays a role in supervising their children and other family members